GAMBARAN HEMODINAMIK SEBELUM DAN SETELAH DILAKUKAN HEMODIALISIS DI LABUANG BAJI MAKASSAR - Nur Febrianti; Alia Andriani; Nur Ramdani Kiri (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2021)
Objective: to determine the comparative analysis of a warm compress to the decline in hospital Labuang phlebitis scale Makassar Baji Year 2014. Methods kind of research was Quasi Exsperimen diruang INAPA Hospital Makassar Baji Labuang with sampling technique is purposive sample of 10 treatments sampling.jumlah and 10 control. Result: the effect of giving warm compresses on the phlebitis decrease in the treatment and control group by using warm water compresses with temperature of 34 degrees in 20 minutes turned out to decrease the phlebitis scale. Discussion: The results of this study suggest to nurses to always provide warm water compresses to patients with phlebitis. Conclusion: in this study the conclusion is after administration and before giving warm compresses on the phlebitis patient in the hospitalization room. Salinity of Makassar Beds can be known that the respondent has decreased